Pengaruh Konflik Kerja dan Keseimbangan Kehidupan Kerja terhadap Produktivitas Karyawan PT PLN Up 3 Surakarta - Lestari, Dian (Advances In Social Humanities Research, 2024)
Research objectives: (1) Analyze the influence of work conflict on employee productivity at PT. PLN UP 3 Surakarta. (2) Analyzing the influence of work-life balance on PT employee productivity. PLN UP 3 Surakarta. (3) Knowing which variables influence the productivity of PT employees. PLN UP 3 Surakarta. This research was conducted using a quantitative approach with a sample size of 60 respondents. The instrument used by researchers is a questionnaire. Quality testing of research instruments is validity and reliability testing. Data analysis uses descriptive analysis, while hypothesis testing uses multiple linear regression analysis with the help of Statistical Package for Social Sciences (SPSS) 23. The results of the research explain that there is a positive and significant relationship between work conflict and work-life balance on employee productivity with an R-value Square is 0.467 or 46.7%. Meanwhile, the remaining 53.3% was influenced by other variables not studied such as communication, leadership, organizational culture and work environment.